Extending synchrotron SAXS instrument ranges through addition of a portable, inexpensive USAXS module with vertical rotation axes. (2nd May 2021) - Pauw, Brian R.; Smith, Andrew J.; Snow, Tim; Shebanova, Olga; Sutter, John P.; Ilavsky, Jan; Hermida-Merino, Daniel; Smales, Glen J.; Terrill, Nicholas J.; Thünemann, Andreas F.; Bras, Wim
Abstract : This compact, Creative‐Commons‐licensed ultra‐SAXS module, augments existing high‐performance SAXS/WAXS synchrotron instruments, so that larger structures may be measured. Its functionality is demonstrated at the I22 beamline at Diamond Light Source, where the combined USAXS/SAXS/WAXS range of an alumina membrane, a porous carbon catalyst and silica, covers over four decades in scattering angle. Abstract : Ultra‐SAXS can enhance the capabilities of existing synchrotron SAXS/WAXS beamlines. A compact ultra‐SAXS module has been developed, which extends the measurable q ‐range with 0.0015 ≤ q (nm −1 ) ≤ 0.2, allowing structural dimensions in the range 30 ≤ D (nm) ≤ 4000 to be probed in addition to the range covered by a high‐end SAXS/WAXS instrument. By shifting the module components in and out on their respective motor stages, SAXS/WAXS measurements can be easily and rapidly interleaved with USAXS measurements. The use of vertical crystal rotation axes (horizontal diffraction) greatly simplifies the construction, at minimal cost to efficiency. In this paper, the design considerations, realization and synchrotron findings are presented. Measurements of silica spheres, an alumina membrane, and a porous carbon catalyst are provided as application examples.